Optical detection of gadolinium(iii) ions via quantum dot aggregation. Issue 40 (11th May 2017) - Quinn, Steven D.; Magennis, Steven W.
Abstract : CdTe quantum dot aggregation induced by trivalent metal ions is followed using fluorescence, dynamic light scattering and fluorescence correlation spectroscopy. Abstract : A rapid, sensitive and selective optical readout of the presence of gadolinium(iii ) ions would have a wide range of applications for clinical and environmental monitoring. We demonstrate that water-soluble CdTe quantum dots (QDs) are induced to aggregate by Gd 3+ ions in aqueous solution. By using a combination of photoluminescence spectroscopy, dynamic light scattering and fluorescence correlation spectroscopy (FCS) to monitor quantum dot aggregation kinetics, we correlate the efficiency of the self-quenching process with the degree of aggregation across a broad range of conditions, including different sizes of QDs. We attribute the aggregation to metal binding to the QD's surface ligands and the quenching to intra-aggregate energy transfer between QDs. When the strategy was applied to additional trivalent ions, the aggregation rate varied according to the particular trivalent metal ion used, suggesting that the selectivity can be enhanced and controlled by appropriate design of the capping ligands and solution conditions.